Posterior Migration of Sequestrated Disk Herniation Mimicking Epidural Mass: 2 Case Reports. Issue 2 (May 2016) - Şanal, Bekir; Korkmaz, Mehmet; Can, Fatma; Kaçar, Emre; Işik, Mahmut; Özkan, Yasemin
Abstract : Herniated nucleus pulposus is the most commonly encountered condition in lumbar region. Herniated disk frequently occurs in the anterior epidural region. However, posterior migration of disk body is very rare because of the anatomic structure. When a mass is detected in the posterior epidural region, various etiological factors such as tumors, abscess, and cysts are generally taken into consideration in differential diagnosis other than disk herniation; however, posterior migration of the disk herniation has also similar appearance to these mentioned conditions. In this case report, we aimed to discuss differential diagnosis of 2 patients with sequestrated disk herniation in whom posterior epidural mass was observed in magnetic resonance imaging and to review the literature.